The role of the Kidd-antibodies in posttransfusion reactions - Nikolić Ljubinka I.; Čolak Emina S.; Kadija Saša A.; Ilić-Mostić Tatjana Ž.; Mladenović Nenad N.; Marković Srđan Z.; Kastratović Dragana A.; Stričević Tanja Lj; Bogdanović Gradimir D. (Srpsko lekarsko drustvo, 2019)
Topic: The Kidd blood group (Jk) was discovered in 1951 and according to International Society for blood transfusion (ISBT) the Kidd (Jk) blood group is registered under the number 009. Antigens of the Kidd system are detected only on RBCs and kidney. Incompatibile transfusion in Jk blood group can provoke sensitization and appearance of anti-Jka or anti-Jkb antibodies. Jk antibodies are common cause of delayed hemolytic transfusion reactions (DHTRs). Although Kidd antibodies can lead to acute reactions, kidney damage and hemoglobinuria are very rare. More important is Kidd-antibody ability for delayed hemolytic reactions. The aim is to underline Jka antibodies laboratory characteristics, their role in delayed posttransfusion reactions and possible complications of blood transfusions. The topic position in scientifi c/professional public: Kidd-antibodies, usually, destroy transfused red cells after a variable period of between 7 and 21 days. DHTR is the result of anti-Jka antibodies tendency to fall rapidly to undetectable levels even after incompatible transfusion. Anti-Jka has been reported as reason for kidney transplant rejection. There were examples of anti-Jka that react only when preservatives such as p-hydroxybenzoic acid (parabens), Na-azide or related compounds, antibiotics are present in the reaction mixture. Also, patient's therapy with antibiotics and monoclonal antibodies could cause false positive RBC antibody. Further action needed for better topic covering in future: Except in life threatening condition, reduction of allogenic blood transfusion is recommended. Increase the number of autologous transfusions in all cases when the patient's clinical condition allows. Antigen-free RBC ie universal RBC would be the best choice for transfusion. It is essential to perform extended erythrocyte phenotyping prior to initiation of monoclonal antibodies therapy. As a minimum blood typing for Rh, K, Jka,Jkb, Fya, Fyb and Ss antigens should be done for every patient who is planned to be treated with monoclonal antibodies.Overcoming this problem is very important for patients who are transfusion-dependent or candidates for monoclonal antibody therapy, or candidates for kidney transplantation.